2018
DOI: 10.3221/igf-esis.47.21
|View full text |Cite
|
Sign up to set email alerts
|

A numerical model based on ALE formulation to predict crack propagation in sandwich structures

Abstract: A numerical model to predict crack propagation phenomena in sandwich structures is proposed. The model incorporates shear deformable beams to simulate high performance external skins and a 2D elastic domain to model the internal core. Crack propagation is predicted in both core and external skin-to-core interfaces by means of a numerical strategy based on an Arbitrary Lagrangian-Eulerian (ALE) formulation. Debonding phenomena are simulated by weak based connections, in which moving interfacial elements with da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Cohesive models for sandwich core/skin interfaces were calibrated by means of comparisons with numerical and experimental data for mode I and mode II configurations. They also studied, [25], the influence of inertial effects on debonding phenomena and crack propagation in different core typologies of sandwich structures based on fracture parameters determined experimentally on commercially available foams. Park et al [26] investigated the force-time history curves of impacted sandwich structures and concluded that the damage resistance appears to be dependent on both the facesheet materials and core thickness: the lower the stiffness becomes, the greater the core thickness affects the impact resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Cohesive models for sandwich core/skin interfaces were calibrated by means of comparisons with numerical and experimental data for mode I and mode II configurations. They also studied, [25], the influence of inertial effects on debonding phenomena and crack propagation in different core typologies of sandwich structures based on fracture parameters determined experimentally on commercially available foams. Park et al [26] investigated the force-time history curves of impacted sandwich structures and concluded that the damage resistance appears to be dependent on both the facesheet materials and core thickness: the lower the stiffness becomes, the greater the core thickness affects the impact resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Once that the predicted crack propagation angle is larger than the tolerance value, a re-meshing procedure is required. This procedure, extensively described in a previous authors' work developed in static framework [27], is made by proper script files implemented in a MATLAB® environment, which manages the numerical procedure. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the present work, the evaluation of the load carrying capacity is performed by a mass proportional force distribution. As known, by using implicit time integration schemes [22,23], the softening behavior, which is typically expected by the CDP, is hardly reproducible, since non-convergent behaviors of the solution might have happened. For these reasons, several attempts where an explicit time integration scheme to solve highly nonlinear systems under quasistatic or dynamic loads condition have been proposed in [24][25][26].…”
Section: Nonlinear Pushover Analysismentioning
confidence: 99%